Translation Peculiarities of Economic Terms from English to Tatar Language. - KHASANZIANOVA, GULNARA ILGIZOVNA; SHAKIROVA, DILYARA SHAMILEVNA (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article is devoted to the study of the translation peculiarities of economic terms from english into the Tatar language in terms of their nominative structure. Difficulties in economic terminology translating are one of the main communication obstacles in the field of economic sciences. The material of the study was the English texts on economic themes. The terms were selected from newspapers such as The Wall Street Journal and The Economist. The study has practical importance, since the results can be used in classes of basic foreign language; they can also be practical materials in compiling a thematic dictionary.RESUMEN El artículo está dedicado al estudio de las peculiaridades de la traducción de términos económicos del inglés al idioma tártaro en términos de su estructura nominativa. Las dificultades en la traducción de la terminología económica son uno de los principales obstáculos de comunicación en el campo de las ciencias económicas. El material para el estudio fueron los textos en inglés sobre temas económicos. Los términos fueron seleccionados de periódicos como The Wall Street Journal, y The Economist. El estudio tiene una importancia práctica, ya que los resultados pueden usarse en clases de lengua extranjera básica;  también pueden ser materiales prácticos para compilar un diccionario temático